Effect of glucose and palmitate environment on proliferation and migration of PC3-prostate cancer cells - Rezende, Lívia Prometti; Galheigo, Maria Raquel Unterkircher; Landim, Breno Costa; Cruz, Amanda Rodrigues; Botelho, Françoise Vasconcelos; Zanon, Renata Graciele; Góes, Rejane Maira [UNESP]; Ribeiro, Daniele Lisboa (Wiley, 2019)
Recent studies have been trying to find out how diet and metabolic changes such as dyslipidaemia, hyperglycaemia, and hyperinsulinaemia can stimulate cancer progression. This investigation aimed to evaluate the effect of high concentrations of fatty acids and/or glucose in tumour prostate cells, focusing on the proliferation/migration profile and oxidative stress. PC3 cells were treated with high concentration of saturated fatty acid (palmitate, 100 µM), glucose (220 mg/dL), or both for 24 or 48 h. Results demonstrated that PC3 cells showed a significant increase in proliferation after 48 h of treatment with glucose and palmitate+glucose. Cell proliferation was associated with reduced levels of AMPK phosphorylation in glucose group at 24 and 48 h of treatment, while palmitate group presented this result only after 48 h of treatment. Also, there was a significant increase in cell migration between time 0 and 48 h after all treatments, except in the control. Catalase activity was increased by palmitate in the beginning of treatment, while glucose presented a later effect. Also, nitrite production was increased by glucose only after 48 h, and the total antioxidant activity was enhanced by palmitate in the initial hours. Thus, we conclude that the high concentration of the saturated fatty acid palmitate and glucose in vitro influences PC3 cells and stimulates cellular activities related to carcinogenesis such as cell proliferation, migration, and oxidative stress in different ways. Palmitate presents a rapid and initial effect, while a glucose environment stimulates cells later on, maintaining high levels of cell proliferation.
Keywords: AMPK; cell proliferation; glucose; palmitate; prostate cancer; saturated fatty acid